PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF BERBASIS TGT BERBANTUAN CANVA DAN QR CODE PADA MATA PELAJARAN IPAS KELAS V SD - Nila Latifaturrohmah; Frita Devi Asriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
One of the most efficient ways to improve student engagement and comprehension is through technology-based interactive learning activities. The state of schools that still do not fully employ learning media and the unequal usage of technology to enhance the effectiveness of learning activities are the driving forces behind this study. As a result, creating technology-based educational materials specifically, interactive videos is essential. This study intends to characterize the applicability and validity of interactive video learning materials based on TGT that are aided by QR Codes and Canva. Development research (R&D) is the term for this kind of study. The present study used the ADDIE model, which has the following components: analysis, design, development, implementation, and evaluation. Fifteen fifth-grade students from SDN 3 Mojosari served as the research subjects. Validation sheets for media and material experts as well as observation sheets are the research tools utilized. Both qualitative and quantitative data kinds were acquired.Media experts gave the TGT-based interactive video learning materials, which were made using Canva and QR Code, an average percentage of 92.8%, and material experts gave them an average percentage of 91.6%, indicating that they were legitimate. The overall proportion of findings qualified as applicable without adjustments. Based on the findings of the data analysis, the TGT-based interactive video learning resources for grade V SD that were produced using Canva and QR Codes are judged to be extremely valid and relevant.